Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jpm11090894
|View full text |Cite
|
Sign up to set email alerts
|

Parental Quality of Life and Involvement in Intervention for Children or Adolescents with Autism Spectrum Disorders: A Systematic Review

Abstract: Previous research has examined several parental, child-related, and contextual factors associated with parental quality of life (QoL) among parents with a child or an adolescent with autism spectrum disorders (ASD); however, no systematic review has examined the relationship between parental QoL and parental involvement in intervention. To fill this gap, a systematic review was conducted using four electronic databases and checked reference lists of retrieved studies. Records were included in the systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 71 publications
(128 reference statements)
2
23
0
5
Order By: Relevance
“…Autism spectrum disorder (ASD) is described as a group of neurodevelopmental diseases, the symptoms of which begin during early childhood and typically last throughout a person’s life. The causes and risk factors that make children more likely to develop ASD are manifold, including environmental, biological, and genetic influences [ 1 ]. Fragile X Syndrome (FXS) is the most frequent form of inherited X-linked pathology and the first monogenic cause of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is described as a group of neurodevelopmental diseases, the symptoms of which begin during early childhood and typically last throughout a person’s life. The causes and risk factors that make children more likely to develop ASD are manifold, including environmental, biological, and genetic influences [ 1 ]. Fragile X Syndrome (FXS) is the most frequent form of inherited X-linked pathology and the first monogenic cause of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…This may prompt them to re-examine whether they are sufficiently effective in their parental role. Additionally, the inability to balance between different obligations can result in feelings of guilt and mourning of the lost opportunities, demotivation for daily activities, low satisfaction and feeling of vitality, a negative self-perception and low self-esteem, as well as depression and reduced quality of life [ 5 , 6 , 7 , 8 ]. Even though most families adapt to the situation over time and find their own routine, it has been confirmed that parental perception of the quality of life depends on the severity of the illness and the extent of disability of the child [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Developmental difficulties such as Down syndrome (DS), autistic spectrum disorders (ASD) and cerebral palsy (CP) are among the most common chronic conditions in childhood [ 11 ]. It was shown that parents of children with ASD have higher risk for experiencing chronic psychological stress, and thus impaired QOL, in comparison to parents of children with typical development (TD) and without chronic diseases [ 7 , 12 , 13 ], and compared to parents of children with Down syndrome [ 14 ]. A systematic review showed that parents of children with infantile cerebral palsy had lower QOL, along with higher levels of stress and depression, compared to the parents of TD children [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Correspondingly, given that it is recognized that parents and families are essential to the well-being of children with ASD, researchers, policymakers, and service providers need to recognize the importance of supporting them and allowing for their involvement in the intervention for their children. This may be one way to improve parents’ QoL, 15 especially in Malaysia where currently there is limited support from the public and private sectors in providing more suitable centers and facilities to assist them in their difficult situation. 9 …”
Section: Introductionmentioning
confidence: 99%